Mejoramiento genético de la papa para resistencia a las heladas. - Devaux, A.; García, W.; Carrasco, E.; Mendoza, O.; García, Eva; Estrada Ramos, N. (Federación. Colombiana de Productores de Papa - FEDEPAPA, 2018)
Papa-Solanum tuberosum